Cetuximab hypersensitivity infusion reactions: Incidence and risk factors*. (September 2013) - Hopps, Sarah; Medina, Patrick; Pant, Shubham; Webb, Ryan; Moorman, Meredith; Borders, Emily
Introduction: Cetuximab is a chimeric mouse-human (30:70) IgG1 monoclonal antibody that competitively inhibits the binding of epidermal growth factor. Cetuximab is generally well tolerated; however, hypersensitivity infusion reactions have been reported. The incidence at the University of Oklahoma was currently unknown, though anecdotally high. The purpose of this study was to determine the incidence of severe HIRs and secondarily to determine risk factors for cetuximab-induced hypersensitivity infusion reactions. Methods and results: A retrospective chart review was conducted and included all patients that received cetuximab from 2005 to 2010 at the outpatient clinics of the Oklahoma University Health Sciences Center. A total of 153 patients were included in the analysis. The overall incidence proportion of severe hypersensitivity infusion reactions was 12.4%. Male patients had an increased incidence of severe hypersensitivity infusion reactions compared to female patients (20.6% vs. 5%, p = 0.0036). Current smokers had an increased incidence of severe hypersensitivity infusion reactions of 23.6% when compared to never smokers or former smokers, p = 0.0012. Cervical cancer had a significantly decreased risk of severe hypersensitivity infusion reactions when compared to other tumor types (5.3% vs. 16.7%, p = 0.0387). Multivariate analysis identified risk factors associated with severe HIRs to be: male gender, RR = 3.9, p = 0.01 and current smokers, RR = 3.98, p = 0.0048. Conclusion: Patients at the University of Oklahoma had an increased incidence of severe hypersensitivity infusion reactions when compared to the national average. Male patients and current smokers were found to be at increased risk for severe hypersensitivity infusion reactions in our study. Further investigation is warranted.